OPPORTUNITIES AND CHALLENGES ARISING FROM ACADEMIC FAST-TRACK PROGRAMS: A LITERATURE REVIEW (Journal of Foreign Language Studies, 2023)
There is a paucity of literature synthesing and systematically categorising fast-track programs’ opportunities, challenges, and support structures in Vietnam. To close this gap, the current study offers such a synthesis via thematically analysing 11 carefully selected journal articles about different fast-track programs worldwide. Findings show that students gained shortand long-term benefits, experienced difficulties, and received peer-teacher-institution-family support in academical, emotional, social, and administrative aspects. Recommendations are then made for successful implementation of fast-track programs as well as for further research. This study’s findings are particularly useful for newly executed fast-track programs and can be used as baseline analytical framework of a primary research investigating similar topics.
Keywords: fast-track learning; fast-track programs; accelerated learning; accelerated programs; acceleration; early college entrance